Prostasin Impairs Epithelial Growth Factor Receptor Activation to Suppress Dengue Virus Propagation. (23rd November 2018) - Lin, Chun-Kuang; Tseng, Chin-Kai; Wu, Yu-Hsuan; Lin, Chun-Yu; Huang, Chung-Hao; Wang, Weng-Hung; Liaw, Chih-Chuang; Chen, Yen-Hsu; Lee, Jin-Ching
Abstract: Background: Dengue virus (DENV), a common and widely spread arbovirus, causes life-threatening diseases, such as dengue hemorrhagic fever or dengue shock syndrome. There is currently no effective therapeutic or preventive treatment for DENV infection. Methods: Next-generation sequencing analysis revealed that prostasin expression was decreased upon DENV infection. Prostasin expression levels were confirmed by real-time quantitative polymerase chain reaction in patients with dengue fever and a DENV-infected mice model. Short hairpin RNA against EGFR and LY294002 were used to investigate the molecular mechanism. Results: Based on clinical studies, we first found relatively low expression of prostasin, a glycosylphosphatidyl inositol-anchored membrane protease, in blood samples from patients with dengue fever compared with healthy individuals and a high correlation of prostasin expression and DENV-2 RNA copy number. DENV infection significantly decreased prostasin RNA levels of in vivo and in vitro models. By contrast, exogenous expression of prostasin could protect ICR suckling mice from life-threatening DENV-2 infection. Mechanistic studies showed that inhibition of DENV propagation by prostasin was due to reducing expression of epithelial growth factor receptor, leading to suppression of the Akt/NF-κB–mediated cyclooxygenase-2 signaling pathway. Conclusion: Our results demonstrate that prostasin expression is a noteworthy clinical feature and a potential therapeutic target against DENV infection. Abstract : Clinically, prostasin expression and DENV-2 RNA copy number showed a significant negative correlation. Prostasin overexpression reduced DENV-2 propagation in vivo and in vitro. The molecular mechanism of prostasin against DENV-2 was due to suppression of EGFR/Akt/NF-κB–mediated cyclooxygenase-2 expression.